KAJIAN PERILAKU BEKANTAN (Nasalis larvatus) PADA KONSERVASI EKS SITU DI PT INDOCEMENT TARJUN - Teguh Iman Basoeki; Yudi Firmanul Arifin; Moehansyah Moehansyah; Abdi Fithria (EnviroScienteae, 2015)
Research was aimed to study the behavior of Bekantan (Nasalis larvatus) in ex-situ conservation at PT Indocement Tarjun. The research of Bekantan’s behavior used several methodology. Firstly, it was observed several kinds and compositions of daily food which was consumed by Bekantan. Secondly, it was also observed the average daily behavior such as : the movement, the visual body condition and the growth in weight and height of Bekantan. The Observations were done for 2 months in 4 sample of the research. The results were compared to the Bekantan’s behavior which lived in its nature habitat. The results showed that there was no difference of its behavior in the study of food composition between the  Bekantan in ex-situ conservation compare to the Bekantan in its nature habitat. In average,  Bekantan in ex-situ conservation ate 76% leaves’tip. It was also investigated that several kinds of food eaten by Bekantan in ex-situ conservation, such as : “balaran” leaf ( Ipomea sp ), “kacangan” leaf ( Calopogonium caerulium), which are usually planted as cover crop, and “ketapang’s” tip of leaf ( T. catappa ). The daily activity of Bekantan’s behavior in ex-situ conservation was shown that there was no difference of its behavior compare to the Bekantan in its nature habitat. The Bekantan in its nature habit was mainly doing no activity, except resting and sleeping. The Bekantan in ex-situ conservation had more activity of movement. They moved, jumped, swinged, and walking using 2 or 4 feet. The conclusion of this research was found a similar eating habits of Bekantan in ex-situ conservation at PT Indocement Tarjun and Bekantan which lived in its habit. The investigation of food compositions showed that about 76% of both Bekantan ate leaves. The leaves’s tip could get from both tips of tree leaf or vegetables. There was a changing of Bekantan’s behavior in term of its movement. Bekantan in ex-situ conservation moved with jumping, swinging, and walking with 2 or 4 feet, hanging, and propagation.